The Influence of Employer Branding on the Interest of Millennial and Gen Z Job Seekers - Yeheskial Nggandung (Maneggio, 2025)
Employer branding has increasingly become a strategic pillar for attracting Millennial and Generation Z job seekers in the digital recruitment era. This study analyzes the effect of employer branding on job application intention among Millennial and Gen Z candidates using a quantitative PLS-SEM approach with 100 respondents. The results indicate that employer branding has a positive and significant effect on job application intention, with a path coefficient of 0.691 and a p-value of 0.000. Beyond creating organizational attractiveness, employer branding fosters organizational trust by reducing uncertainty in career decision-making, enabling candidates to feel secure about joining the company. Positive perceptions of workplace culture, organizational values, and career development opportunities encourage Millennials and Gen Z to apply for jobs. This study highlights employer branding not only as a communication strategy but also as a psychological mechanism to secure high-quality talent in competitive labor markets.